Staatliche Regulierung in vertikal verbundenen Industrien - eine spieltheoretische Analyse - N, N

Pricing and Revenue Sharing of Bundles Using Game Theoretical Concepts - N, N

Strategic Formation of Customer Relationship Networks - Brangewitz, Sonja; Haake, Claus-Jochen; Möhlmeier, Philipp
We analyze the stability of networks when two intermediaries strategically form costly links to customers. We interpret these links as customer relationships that enable trade to sell a product. Equilibrium prices and equilibrium quantities on the output as well as on the input market are determined endogenously for a given network of customer relationships. We investigate in how far the substitutability of the intermediaries' products and the costs of link formation influence the intermediaries' equilibrium profits and thus have an impact on the incentives to strategically form relationships to customers. For networks with three customers we characterize locally stable networks, in particular existence is guaranteed for any degree of substitutability. Moreover for the special cases of perfect complements, independent products and perfect substitutes, local stability coincides with the stronger concept of Nash stability. Additionally, for networks with n customers we analyze stability regions for selected networks and determine their limits when n goes to infinity. It turns out that the shape of the stability regions for those networks does not significantly change compared to a setting with a small number of customers.

Competition and Product Innovation of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen
On an intermediate goods market we allow for vertical and horizontal product differentiation and analyze the influence of simultaneous competition for resources and customers on the market outcome. Asymmetries between intermediaries cannot arise just from distinct product qualities, but also from different production technologies. The intermediaries face either price or quantity competition on the output market and a monopolistic input supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Considering product innovation for symmetric productivities we derive equilibrium conditions on the investment costs and compare price and quantity competition. It turns out that on the one hand there exist product qualities and degrees of horizontal product differentiation for complements such that asymmetric investment equilibria fail to exist. On the other hand we find that there also exist product qualities and degrees of horizontal product differentiation for substitutes such that existence can be guaranteed if the investment costs are chosen accordingly.

Bilateral matching and bargaining games - Mikroökonomie, Lehrstuhl

Robust Equilibria in Location Games - Buechel, Berno; Röhl, Nils (European Journal of Operational Research)
In the framework of spatial competition, two or more players strategically choose a locationin order to attract consumers. It is assumed standardly that consumers with the same favorite location fully agree on the ranking of all possible locations. To investigate the necessity of this questionable and restrictive assumption, we model heterogeneity in consumers’ distance perceptions by individual edge lengths of a given graph. A proﬁle of location choices is called a “robust equilibrium” if it is a Nash equilibrium in several games which diﬀer only by the consumers’ perceptions of distances. For a ﬁnite number of players and any distribution of consumers, we provide a full characterization of all robust equilibria and derive structural conditions for their existence. Furthermore, we discuss whether the classical observations of minimal diﬀerentiation and ineﬃciency are robust phenomena. Thereby, we ﬁnd strong support for an old conjecture that in equilibrium ﬁrms form local clusters.

Praktikabilität des Adjusted Winner Verfahrens bei variablem Status Quo- Punkt und exogenen Einflüssen - Streck, Thomas

Simultane bilaterale Verhandlungen - Zur Zusammenstellung eines Sortiments - N, N

Cournot-Nash-Bertrand Wettbewerb im serviceorientierten Internet - N, N

Multilaterale Verhandlungen aus Produzentensicht - N, N